The comparison of perinatal clinical characteristics between severe small for gestational age and mild small for gestational age according to the latest birth curve in ChinaAJOG Global Reports at a Glance - Yongbing Guo, PhD; Huijing Zhang, PhD; Jinling Kang, MD; Yu Sun, PhD; Huixia Yang, PhD (AJOG Global Reports, 2025)
BACKGROUND: Small for gestational age(SGA) is associated with increased risks of short-term complications and neonatal death.The severity of SGA can be grouped according to the weight of newborns. OBJECTIVE: This study aimed to explore the perinatal clinical characteristics of small for gestational age and to compare the predictive value of 2 growth curves for adverse neonatal outcomes. STUDY DESIGN: A total of 131 neonates diagnosed with small for gestational age at Peking University First Hospital from January to June 2021 were included in the study. According to the percentile of birthweight, the neonates were divided into 2 groups: 105 in the mild small-for-gestational-age group (birthweight between the 3rd and 10th percentile) and 26 in the severe small-for-gestational-age group (birthweight lower than the 3rd percentile). The general data and clinical information of mothers and neonates were collected to compare the differences between maternal complications and neonatal outcomes in different groups of small for gestational ages. RESULTS: The incidence of preeclampsia and preterm delivery in the severe small for gestational age group was significantly higher than that in the mild small-for-gestational-age group. The incidence of neonatal hypoglycemia and neonatal anemia in the severe small-for-gestational-age group was significantly higher than that in the mild small-for-gestational-age group. The maternal body weight and body mass index in the mild small-for-gestational-age group were lower than those in the severe small-for-gestational-age group. In addition, the 2020 birthweight curve had better sensitivity, specificity, positive predictive value, and negative predictive value in predicting adverse neonatal outcome than the 2015 birthweight curve. CONCLUSION: The risk of neonatal complications was significantly higher in the severe small-for-gestational-age group. Perinatal monitoring of small-for-gestational-age patients should be strengthened. Mild small for gestational age was associated with lower maternal body mass index. The 2020 neonatal curve is more valuable for adverse neonatal outcome prediction.